Implementation of Human Resource Management in Undergraduate Teacher Development at Modern Islamic Institution Darussalam Gontor Campus 2 - Taufik Rizki Sista; Muhammad Rizal Muttaqin; Agung Wijaksono (At-Ta'dib, 2022)
This research focuses on the model of developing undergraduate teachers and implementing HR management in accommodating the process of fostering undergraduate teachers at Pesantren Gontor campus 2. The novelty in this research lies in the aspect of fostering undergraduate students as Islamic boarding school teachers and their empowerment in helping manage Islamic boarding schools. The aims of this study are to (1) find out the pattern of fostering undergraduate teachers in teaching and learning activities in Islamic boarding schools, and(2) to describe the role of HR management in maintaining the quality and performance of undergraduate teachers in teaching and learning activities. This research utilized a qualitative research method with a phenomenological approach. The data collection technique employs the Triangulation technique from Milles and Huberman, such as Observation, Interview, and Documentation. The data analysis technique utilized is a triangulation analysis technique consisting of data reduction, data presentation, and data verification. The results of this study reveal that the leadership of the Pesantren Gontor Campus 2 implements HR management in teacher development with the following points: Planning: Budgeting, Programming, Decision Making, and Forecasting. Organizing: Structuring, Assembling resources, Staffing. Actuating: Coordinating, Directing, Commanding, Motivating, Leading, Stimulating. Supervision (Controlling): Monitoring, Appraising. Evaluating (Evaluation): Reporting.